Interobserver Variation in the Diagnosis of Neurologic Abnormalities in the Horse. (9th September 2017) - Saville, W.J.A.; Reed, S.M.; Dubey, J.P.; Granstrom, D.E.; Morley, P.S.; Hinchcliff, K.W.; Kohn, C.W.; Wittum, T.E.; Workman, J.D.
Abstract : Background: The diagnosis of equine protozoal myeloencephalitis (EPM) relies heavily on the clinical examination. The accurate identification of neurologic signs during a clinical examination is critical to the interpretation of laboratory results. Objective: To investigate the level of agreement between board‐certified veterinary internists when performing neurologic examinations in horses. Animals: Ninety‐seven horses admitted to the Veterinary Teaching Hospital at The Ohio State University from December 1997 to June 1998. Methods: A prospective epidemiologic research design was used. Horses enrolled in the study were examined by the internist responsible for care of the horse, and later by an internist who was not aware of the presenting complaint or other patient history. Data were analyzed by descriptive statistics, and kappa ( K ) statistics were calculated to assess interobserver agreement. Results: Ninety‐seven horses were enrolled in the study. Overall, examiners, also referred to as observers, agreed that 60/97 (61.9%) were clinically abnormal, 21/97 (21.6%) were clinically normal, and the status of 16/97 (16.5%) of horses was contested. There was complete agreement among the examiners with regard to cranial nerve signs and involuntary movements. Disagreement involving severity of clinical signs occurred in 31 horses, and 25 of those horses (80.6%) were considered either normal or mildly affected by the primary observer. When examining the results of all paired clinical examinations for 11 different categories, there was wide variability in the results. When examiners rated the presence or absence of any neurologic abnormalities, lameness, or ataxia, the agreement among observers was either good or excellent for 80% of horses. When assessing truncal sway, the agreement among observers was good or excellent for 60% of the horses. When examining the horses for asymmetry of deficits, agreement was either good or excellent for 40% of the horses. Agreement among observers was excellent or good for only 20% of the horses when assessing muscle atrophy, spasticity (hypermetria), and overall assessment of the severity of neurologic abnormalities. Conclusions and Clinical Importance: This study underscores the subjectivity of the neurologic examination and demonstrates a reasonable level of agreement that may be achieved when different clinicians examine the same horse.